Establishment of persistent infection with foot-and-mouth disease virus in BHK-21 cells - Huang, Xuan (BioMed Central, 2011)
BACKGROUND: Foot-and-mouth disease virus (FMDV) is able to cause persistent infection in ruminants besides acute infection and disease. Since the mechanisms of viral persistence and the determining factors are still unknown, in vitro systems help explore and reveal mechanisms of persistence in vivo by providing useful models for the study of RNA genome mutations and evolution. Ammonium chloride, a lysosomotropic agent that raises intralysosomal pH, reduces the yield of FMDV during infection of BHK-21 cells. RESULTS: The persistent infection with FMDV serotype O in BHK-21 cells was selected and established readily after treatment of ammonium chloride that acts primarily on the cells. Intact virions were observed located inside the endosomes. Viral genome RNAs and specific proteins were detected in the persistent cells to validate the establishment of viral persistence. Infection of the persistent viruses could not form plaques in host cells but virulence was enhanced. Basing on analysis and comparison of cDNA sequences of resident viruses and wild type viruses, 15 amine acid mutations were found, all of which were located in nonstructural proteins rather than in structural proteins. CONCLUSIONS: Therefore, persistent infection of cell cultures with FMDV is successfully established with some distinctive features. It would be worthwhile to further investigate the mechanisms of viral persistence.